MANAJEMEN KURIKULUM BERBASIS BUDAYA - Widodo, Petrus (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2025)
This study aims to describe culture-based curriculum management at SMPN 3 Banguntapan Bantul, reviewed from the aspects of curriculum planning, curriculum implementation, curriculum evaluation, as well as supporting and inhibiting factors in culture-based curriculum management. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. Data sources include the school principal, vice principal, and teachers. Data analysis was conducted using the interactive model by Miles et al. (2014), which includes data condensation, data presentation, and conclusion drawing. Data validity was ensured using source triangulation and member checking techniques. The results of the study indicate that: (1) curriculum planning is carried out through workshops involving the principal, vice principal for curriculum, and teachers, and is developed based on the school's vision and mission; (2) curriculum implementation is carried out through the internalization of cultural values into academic and non-academic activities; (3) Curriculum evaluation focuses on changes in student character and improvements in academic and non-academic achievements; and (4) Supporting factors for curriculum implementation include teacher motivation, community support, and government policies; while the inhibiting factors stem from differing perceptions among teachers. Support from various parties, especially the government, is a crucial aspect in the success of implementing culture-based curriculum management at this school.